Answer:
C. (-1, 3)
Step-by-step explanation:
Label the 2 equations:
5y= 7x +22 -----(1)
x= -6y +17 -----(2)
Substitute (2) into (1):
5y= 7(-6y +17) +22
5y= -42y +119 +22 <em>(</em><em>Expand</em><em> </em><em>bracket</em><em>)</em>
5y= -42y +141 <em>(</em><em>Simplify</em><em>)</em>
42y +5y= 141 <em>(</em><em>+</em><em>42y</em><em> </em><em>on</em><em> </em><em>both</em><em> </em><em>sides</em><em>)</em>
47y= 141
y= 141 ÷47 <em>(</em><em>÷</em><em>4</em><em>7</em><em> </em><em>on</em><em> </em><em>both</em><em> </em><em>sides</em><em>)</em>
y= 3
Substitute y= 3 into (2):
x= -6(3) +17
x= -18 +17
x= -1
Thus, the solution is (-1, 3).
It would be letter. b....
Answer:
y=4/3-1/6x
Step-by-step explanation:
1) subtract "x" from both sides:
6y=8-x
2)divide by 6 on both sides(EVERYTHING WILL BE DIVIDED BY 6)
6y/6=(8-x)/6
y=(8-x)/6
2)simplify:
y=4/3-x/6
Answer:
Step-by-step explanation:
you will need to do:
j/9*2=2j/9